Galactosylated streptavidin for improved clearance of biotinylated intact and F(ab')2 fragments of an anti-tumour antibody. - Marshall, D. (Nature Publishing Group, 1995)
Persistence of high levels of radiolabelled antibody in the circulation is a major limitation of radioimmunotherapy. Biotinylation of the radiolabelled anti-tumour antibody followed by administration of streptavidin is known to give much improved tumour to blood ratios as the radioantibody is complexed and subsequently cleared via the reticuloendothelial system, although prolonged splenic uptake is a problem. We have investigated the effect on the clearance pattern and tumour localisation of a 125I-labelled biotinylated anti-CEA antibody (A5B7) after administration of a galactosylated form of streptavidin (gal-streptavidin) in nude mice bearing a human colon carcinoma xenograft. Fifteen minutes to 1 h after gal-streptavidin administration the complexes were cleared via the liver alone (as opposed to liver and spleen after native streptavidin). Twenty-four hours after administration of gal-streptavidin, the tumour to blood ratio for biotinylated A5B7 IgG increased from 2.9 to 13.2 and for biotinylated F(ab')2 fragments an increase from 4.9 to 33.2 was achieved. The reduction in tumour accumulation of F(ab')2 24 h after injection of the clearing agent was less than that seen with intact antibody. Injection of asialofetuin inhibited clearance, confirming that removal of the gal-streptavidin-biotinylated antibody complexes from the blood was via the asialoglycoprotein receptor on liver hepatocytes. Therefore, galactosylation of the streptavidin clearing agent allows rapid removal of radiolabelled biotinylated antibodies via the liver asialoglycoprotein receptor, as opposed to the reticuloendothelial system. IMAGES: